Language, Sex and Social Structure - Clark, J. author. aut Link
X, 157 p.
Keywords: This book offers an innovative way of doing critical discourse analysis that focuses on the performatively produced concepts and social structures that support oppressive attitudes in a community. It draws upon ethnographic data from a women's field hockey club to examine players' homophobic attitudes towards lesbians on the team.